THE EFFECT OF FINANCIAL LITERACY, FINANCIAL PLANNING, AND RISK TOLERANCE ON INVESTMENT DECISIONS WITH FINANCIAL TECHNOLOGY AS A MODERATING VARIABLE (STUDY ON GENERATION Z IN DKI JAKARTA) - Pradipta, Mahendra Aulia (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to analyze the effect of financial literacy, financial planning, and risk tolerance on investment decisions with financial technology as a moderating variable. This study is a quantitative study with a purposive sampling technique. The population of this study is Generation Z in DKI Jakarta Province with a sample of 204 people. The data is collected using a questionnaire prepared in Google Forms. The data is analyzed using PLS-SEM (Partial Least Square - Structural Equation Modeling) using SMARTPLS application Version 4. The results showed that financial literacy and financial planning have a significant positive effect on investment decisions. However, risk tolerance does not affect investment decisions. Furthermore, the role of financial technology as a moderating variable can strengthen the influence of financial planning and risk tolerance, but not financial literacy.